Syntenic block overlap multiplicities with a panel of reference genomes provide a signature of ancient polyploidization events. (December 2015) - Zheng, Chunfang; Santos Muñoz, Daniella; Albert, Victor; Sankoff, David
Abstract Background Following whole genome duplication (WGD), there is a compact distribution of gene similarities within the genome reflecting duplicate pairs of all the genes in the genome. With time, the distribution broadens and loses volume due to variable decay of duplicate gene similarity and to the process of duplicate gene loss. If there are two WGD, the older one becomes so reduced and broad that it merges with the tail of the distributions resulting from more recent events, and it becomes difficult to distinguish them. The goal of this paper is to advance statistical methods of identifying, or at least counting, the WGD events in the lineage of a given genome. Methods For a set of 15 angiosperm genomes, we analyze all 15× 14 = 210 ordered pairs oftarget genome versus reference genome, using SynMap to find syntenic blocks. We consider all sets ofB ≥ 2 syntenic blocks in the target genome that overlap in the reference genome as evidence of WGD activity in the target, whether it be one event or several. We hypothesize that in fitting an exponential function to the tail of the empirical distributionf (B ) of block multiplicities, the size of the exponent will reflect the amount of WGD in the history of the target genome. Results By amalgamating the results from all reference genomes, a range of values of SynMap parameters, and alternative cutoff points for the tail, we find a clear pattern whereby multiple-WGD core eudicots have the smallest (negative) exponents, followed by core eudicots with only the single "γ " triplication in their history, followed by a non-core eudicot with a single WGD, followed by the monocots, with a basal angiosperm, the WGD-freeAmborella having the largest exponent. Conclusion The hypothesis that the exponent of the fit to the tail of the multiplicity distribution is a signature of the amount of WGD is verified, but there is also a clear complicating factor in the monocot clade, where a history of multiple WGD is not reflected in a small exponent.